Prophetic Contrasts: How Durkheim and Girard Affirm the Religious Gift of Peace - Matthew Hallgarth (Religions)
Human beings are prone to violence of all kinds, and they are generally religious. Violence and religion are also thick, difficult-to-define concepts. Are they related? Two seminal thinkers stand as cornerstones in this modern debate. For Emile Durkheim, religion is both a cohesive social force and potential antagonist, uniting the community around ritual norms at odds with outsiders, against whom violence is routinely justified. For Rene Girard, internal mediation of mimetic desire generates rivalries that are assuaged through the ritual sacrifice of scapegoats to hold off social chaos and anomie. Girard writes from within a Christian tradition he argues overcomes this scapegoat doom loop. While Durkheim is a skeptical empiricist about religion, and Girard is a literary man writing from within the Christian tradition, both conclude that religion reduces violence and does not increase it.